Enhancing Vasectomy Adoption in Surabaya Through Multimodal Strategies in Accordance with Government Regulation No. 87 of 2014 - Hilda Yunita Wono (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2024)
Vasectomy, a permanent contraceptive method for men, has historically seen low adoption rates in Indonesia, particularly in Surabaya. To address this, the Indonesian government implemented Regulation No. 87 of 2014, aiming to enhance vasectomy adoption through various strategies. This study examines the effectiveness of these multimodal strategies in increasing vasectomy uptake in Surabaya. This research aims to explore how government regulation and associated multimodal strategies have influenced the adoption rates of vasectomy in Surabaya, identifying key factors that contribute to their effectiveness. Utilizing a qualitative research design, this study conducted in-depth interviews and focus group discussions with healthcare providers, policy makers, and men who have undergone vasectomy. Thematic analysis was employed to interpret the data, providing insights into the perceptions, challenges, and facilitators related to vasectomy adoption. The study found that the integration of educational campaigns, financial incentives, and improved healthcare services significantly influenced the decision-making process of men considering vasectomy. Moreover, cultural attitudes and misconceptions about vasectomy were identified as substantial barriers. The role of healthcare providers in counseling and disseminating accurate information emerged as crucial in overcoming these barriers. The implementation of multimodal strategies under Government Regulation No. 87 of 2014 has positively impacted vasectomy adoption in Surabaya. However, continuous efforts in education and cultural sensitization are necessary to sustain and further enhance these adoption rates. Future research should focus on long-term outcomes and the replication of these strategies in other regions.